Inkarnationen des Bösen im sozialistischen Denken - Pfützner, Robert (Review of ecumenical studies, 2024)
From a Western, democratic perspective, the state socialism that existed until 1989 was criticised, not without justification, as an "evil empire" (Reagan). The Gulag, Pol Pot’s mass murders or Ceaușescu’s dictatorship show evident elements of evil in socialism. However, a different perspective is taken in the essay. From an internal hermeneutic perspective, it asks what forms of evil emerged within socialist thought. From a cultural-theoretical point of view, socialism is seen as a belief system and moral framework. Evil appears in this framework as (1) abstract evil, as (2) evil in others, and as (3) evil in oneself. These three figurations will be illuminated.